WISP-1 drives bone formation at the expense of fat formation in human perivascular stem cells. Issue 1 (December 2018) - Meyers, Carolyn; Xu, Jiajia; Asatrian, Greg; Ding, Catherine; Shen, Jia; Broderick, Kristen; Ting, Kang; Soo, Chia; Peault, Bruno; James, Aaron
Abstract The vascular wall within adipose tissue is a source of mesenchymal progenitors, referred to as perivascular stem/stromal cells (PSC). PSC are isolated via fluorescence activated cell sorting (FACS), and defined as a bipartite population of pericytes and adventitial progenitor cells (APCs). Those factors that promote the differentiation of PSC into bone or fat cell types are not well understood. Here, we observed high expression of WISP-1 among human PSCin vivo, after purification, and upon transplantation in a bone defect. Next, modulation of WISP-1 expression was performed, usingWISP-1 overexpression, WISP-1 protein, orWISP-1 siRNA. Results demonstrated that WISP-1 is expressed in the perivascular niche, and high expression is maintained after purification of PSC, and upon transplantation in a bone microenvironment.In vitro studies demonstrate that WISP-1 has pro-osteogenic/anti-adipocytic effects in human PSC, and that regulation of BMP signaling activity may underlie these effects. In summary, our results demonstrate the importance of the matricellular protein WISP-1 in regulation of the differentiation of human stem cell types within the perivascular niche. WISP-1 signaling upregulation may be of future benefit in cell therapy mediated bone tissue engineering, for the healing of bone defects or other orthopaedic applications.